Sports Massage and Blood Flow Restriction Combined with Cold Therapy Accelerate Muscle Recovery After Fatigue in Mixed Martial Arts Athletes: A Randomized Controlled Trial - Robert Trybulski; Robert Roczniok; Gracjan Olaniszyn; Yaroslav Svyshch; Andryi Vovkanych; Michał Wilk (Journal of Functional Morphology and Kinesiology, 2025)
Objectives: The purpose of this study is to quantitatively evaluate the combined effects of sports massage, blood flow restriction (BFR), and cold therapy on quadriceps recovery in mixed martial arts (MMA) athletes following eccentric exercise, focusing on muscle biomechanical properties, pain, and strength. Methods: This randomized, single-blind clinical trial involved 36 men and women MMA-trained participants, divided into three groups: massage (n = 12) received massage, BFR/cool (n = 12) received combined BFR and cooling, and control (n = 12) received passive rest as a control. The fatigue protocol involved MMA fighters performing five sets of plyometric jumps on a 50 cm box until exhaustion, with 1-min breaks between sets. After that, the massage group received a 20-min massage overall using standardized techniques; BFR/cool underwent a 20-min alternating blood flow restriction (200 mmHg) and cooling treatment with ice bags on the quadriceps; and the final group served as the control group with passive rest and no intervention. Participants were assessed four times—before exercise, immediately after exercise, 24 h post-exercise (after two recovery sessions), and 48 h post-exercise (after four recovery sessions)—for perfusion unit (PU), muscle elasticity, pressure pain threshold (PPT), reactive strength index (RSI), and total quality recovery (TQR). Results: The statistical analysis revealed significant effects of both massage and BFR/cooling interventions across key recovery outcomes, with large effect sizes for time-related changes in RSI (p < 0.0001; η2 = 0.87), elasticity (p < 0.0001; η2 = 0.84), and PPT (p < 0.0001; η2 = 0.66). Notably, post-exercise 48 h values for RSI, elasticity, PU, and TQR were significantly improved in both the massage and BFR/cool groups compared to control (p < 0.05)), while no significant group differences were observed for PPT. Conclusions: The study concludes that both massage and combined blood flow restriction with cooling interventions significantly enhance post-exercise recovery—improving muscle perfusion, elasticity, reactive strength, and perceived recovery—compared to passive rest.